TINJAUAN PELAKSANAAN PEMUTUSAN HUBUNGAN KERJA (PHK) BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Widayanti Widayanti (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
Termination of Employment Relations based on the Law No.13 of 2003 is considered necessary because it often leads to discontent for workers / laborers as has not fulfilled the right of the right workers / labor as it should. It causes the workers to fret when the worker becomes the backbone of the family, the worker / laborer has the responsibility to sustain his economic life, for it needs the protection of workers in the right that should be obtained and how to solve it. From the results of the discussion, some rights were obtained, among others, replacement money, severance pay, and term of employment and settlement of Termination of Employment including Bipartite, Mediation, Conciliation, Arbitase.